1974
DOI: 10.1139/z74-130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diapause and diet on the development of the gonads and accessory reproductive glands of the black blowfly, Phormia regina (Meigen)

Abstract: STOFFOLANO, J. G., JR. 1974. Influence of diapause and diet on the development of the gonads and accessory reproductive glands of the black blowfly, Phormia regina (Meigen). Can. J . Zool. 52: 981-988.Aspects of the reproductive biolo y, including mating, viteIIogenesis, and development of the accessory rcproductiw glands, offfoth nialc and fernalc Phormia regina were ~nvestigated. Non-diapausing adulis showed changes in Xhc female ovaries, plus in the Tat body and accessory rrproducuve gtantls ol' bo~lz sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…For all experiments a standard stock laboratory diet was prepared (Stoffolano, 1974). From this stock 50 ml (50 g) of diet per treatment group was removed using a ladle sampling device (Fisher brand cat no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all experiments a standard stock laboratory diet was prepared (Stoffolano, 1974). From this stock 50 ml (50 g) of diet per treatment group was removed using a ladle sampling device (Fisher brand cat no.…”
Section: Methodsmentioning
confidence: 99%
“…In experiments 1-3, all groups were maintained in the previously described fly rearing room (Stoffolano, 1974). In experiments 4-7, all groups were maintained in a Pervical Growth Chamber (28±2 °C, and 70% r.h. on a 16:8 light:dark photo regime).…”
Section: Methodsmentioning
confidence: 99%
“…chloropyga, an African blowfly recently introduced in Southern Brazil (lmbiriba et al, 1978;Guimariies et al, 1978Guimariies et al, , 1980 is easily reared in laboratory conditions, being an animal particularly useful for biological experiments. Stoffolano (1974) developed an oligidic diet in which the ingredients were whole dried milk, dried brewer's yeast and water. His results have demonstrated satisfactory development of the gonads and accessory reproductive glands of the black blowfly Phormia regina (Meigen).…”
Section: Introductionmentioning
confidence: 99%
“…Pupal and adult fat bodies are found to co-exist in the newly emerged adults of cyclorrhaphous flies of the following genera: Sarcophaga (Day, 1943), Calliphora (Thomsen, 1952), Protophormia (Harlow, 1956), Drosophila (Butterworth, 1972), Musca (Adams and Nelson, 1970), and Phormia (Stoffolano, 1974). Pu- Fig.…”
Section: Pupal Fat Bodymentioning
confidence: 99%
“…Yamamoto et al (1988), using in vitro experiments, showed that either JH III or the JH analog hydroprene stimulated protein synthesis by the ARGs. In P. regina, Stoffolano (1974) indirectly showed that in sugar-fed flies, which have low levels of JH compared to protein-fed flies, the ARGs need higher levels of JH to develop.…”
Section: Accessory Reproductive Glandsmentioning
confidence: 99%